Study on Heat Exchange Structure Design and Propulsion Performance of Solar Thermal Thruster - Haoran Zhang; Minchao Huang; Xiaoping Hu (International Journal of Aerospace Engineering)
This paper designed a platelet heat exchanger in the solar thermal thruster and analyzed the unsteady-state conjugate heat transfer characteristics between heat exchanger and propellant. The conjugate heat transfer (CHT) computational fluid dynamics (CFD) simulation of the 3D model of the platelet under steady-state conditions was carried out with different mass flow rates to find the empirical correlation between the average Nusselt number and the average Reynolds number. The unsteady-state 1D simplified model of the heat exchanger was established using a loose coupling algorithm based on quasi-steady flow domain and finally verified by experiments. The results show that the platelet structure could heat the working medium to more than 2380 K with the heat transfer efficiency of 87% and produce a peak thrust of 0.57 N and specific impulse of 2200 m/s; in steady state, the outlet temperature and heat transfer efficiency of the heat exchanger were stable at 1950 K and 69%. Moreover, 1D model could accurately reflect the real heat exchange situation to a certain extent, the simulation error was less than 5% compared with the 3D model, and the calculation time was greatly shortened, making it more convenient to adjust the heat exchange strategy. The experimental results were consistent with the simulation results at the initial stage of heat exchange, and the difference was mainly reflected in the steady-state stage, which might be caused by the lack of precision of the experimental equipment.